2014
DOI: 10.1902/cap.2014.130084
|View full text |Cite
|
Sign up to set email alerts
|

Do Statin Medications Improve Periodontal Health and/or Outcomes? A Systematic Review

Abstract: Focused Clinical Question: For adult patients (aged ≥30 years) with chronic periodontitis, does the use of 3‐hydroxy‐3‐methyl‐glutaryl coenzyme A reductase inhibitors (statins) improve periodontal health? Clinical Scenario: A 59‐year‐old female with a history of hyperlipidemia presents for periodontal maintenance care. She has been taking a statin medication for 4 years, during which time she received comprehensive periodontal therapy, including regenerative surgery in two quadrants. Post‐surgical evaluation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Various animal studies reported success in bone regeneration when statins were applied locally 23–26 . More recently, one systematic review 27 concluded that use of statins on adult patients ≥30 years of age with chronic periodontitis (CP) showed positive effect on their periodontal status, and that concomitant administration of either systemic or locally delivered statins in adjunct to non‐surgical therapy may help improve periodontal health. Results of another systematic review 28 also indicated beneficial effects of statins and their potential to improve therapeutic effect during PD treatments.…”
mentioning
confidence: 99%
“…Various animal studies reported success in bone regeneration when statins were applied locally 23–26 . More recently, one systematic review 27 concluded that use of statins on adult patients ≥30 years of age with chronic periodontitis (CP) showed positive effect on their periodontal status, and that concomitant administration of either systemic or locally delivered statins in adjunct to non‐surgical therapy may help improve periodontal health. Results of another systematic review 28 also indicated beneficial effects of statins and their potential to improve therapeutic effect during PD treatments.…”
mentioning
confidence: 99%
“…Adult patients ≥ 30 years old with periodontitis showed improvement in their periodontal status on simultaneous administration of either systemic or locally delivered statins in adjunct to nonsurgical therapy. 16 Another systematic review with meta-analyses concluded that statin along with scaling and root debridement promotes significant periodontal parameter improvement. 17 Due to pleiotropic effects of statins, it can evolve as a novel economic, host modulating, and bone anabolic agent in the treatment of periodontitis.…”
Section: Introductionmentioning
confidence: 99%